2021
DOI: 10.36096/ijbes.v3i2.257
|View full text |Cite
|
Sign up to set email alerts
|

The effects of work-life balance and emotional intelligence on organizational commitment mediated by work engagement

Abstract: This study aims to examine the effect of work-life balance and emotional intelligence on organizational intelligence through work engagement. This quantitative research was conducted by distributing questionnaires to 118 employees of Kebumen Branch and Unit of BRI Bank using a purposive sampling method. The data analysis used was Structural Equation Modeling (SEM) using second-order confirmatory with the help of SmartPLS 3.0 application. The results showed that; (1) work-life balance has a positive and signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…The benefits of work-life balance programs, which foster loyalty and improve productivity, have been emphasized by several studies (Bali et al, 2020;Senbursa, 2023). This research corroborates these findings, suggesting that organizations investing in these programs will likely witness lower absenteeism, reduced work-life conflict, and decreased workplace accidents (Muafi & Marseno, 2021). Beyond organizational outcomes, work-life balance is instrumental in mental health, acting as a bulwark against stress and promoting cognitive well-being (Grzywacz & Marks, 2000;Allen et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The benefits of work-life balance programs, which foster loyalty and improve productivity, have been emphasized by several studies (Bali et al, 2020;Senbursa, 2023). This research corroborates these findings, suggesting that organizations investing in these programs will likely witness lower absenteeism, reduced work-life conflict, and decreased workplace accidents (Muafi & Marseno, 2021). Beyond organizational outcomes, work-life balance is instrumental in mental health, acting as a bulwark against stress and promoting cognitive well-being (Grzywacz & Marks, 2000;Allen et al, 2000).…”
Section: Discussionsupporting
confidence: 77%
“…Research has indicated that work-life balance programs improve employee well-being and have a range of other positive effects (Ridwan et al, 2022). For example, these programs have been found to reduce absenteeism and job stress levels, decrease work-life conflict, and lower accident rates (Muafi & Marseno, 2021). Moreover, work-life balance has been linked to increased productivity.…”
Section: The Relationship Between Work-life Balance and Employees' We...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to this, Okolie, Igborhiohwunu, and Omole (2017) assert that employees' commitment to their organisations will grow as their work-life balance improves. The lack of a balance between work and personal life, according to Marseno and Muafi (2021) and Puspitasari, Darwin, and Marseno (2021), is one of the factors that can affect employees' commitment to the organisation. In today's competitive business environment, one of the main struggles of modern firms is organisation commitment and work-life balance (Berk & Gundogmus, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In today's dynamic environment, it is seen that employees facing a heavy workload and long working hours affect the lives of employees and their families (Aslam, 2015), p this naturally will influence work engagement (Marseno & Muafi, 2021). (Dinh, 2020) concluded that leadership style very important in creating a sense of work-life balance for employees, although it may be unavoidable that employees will experience stress in the personal and work lives of employees.…”
Section: Introductionmentioning
confidence: 99%